Peluang Pemanfaatan Kulit Kombucha Berbasis Kulit Kopi dalam Perancangan Produk Home Décor - J. Lianto, Sheren; Hairunnas; Tiffany, Florentina (Universitas Dinamika, 2025)
The abundance of coffee production in Indonesia will also lead to an accumulation of waste from this industry. Approximately 35% of coffee skin waste, also known as cascara, is only used for animal feed and is rarely used for making products. This research aims to find the strongest characteristics of the kombucha skin material made from cascara and make it an innovative and sustainable product. The cascara kombucha skins used in the research have been processed and become ready-to-use skin sheets. These leather sheets are tested for their characteristics using material studies and observations compared to other products to find out what potential developments can be developed. The results show that when illuminated by light, this material has a texture and color that is quite unique and shows potential towards lighting-based products, then by combining multifunctional and ornamental aspects in the product it can add value to the product so that it can compete and have its own appeal compared to other products. other. Apart from being exposed to light, the material also shows potential in laser cutting and interlocking techniques because it can create a pattern from both techniques. With its characteristics, the opportunity for this material is more towards home décor products because its potential is based on lighting, so it can lead to lighting products that add value with multifunctional and ornamental aspects.